Deep Venous Thrombosis - Vieira, Julia Torquato; Neves, Pedro Juan Furtado; Abreu, Phillipe; Mariúba, Jamil Victor de Oliveira [UNESP]; Sobreira, Marcone Lima [UNESP]; Malgor, Rafael (Springer Nature, 2025)
Deep venous thrombosis (DVT) is a disease characterized by the presence of a thrombus inside one of the veins of the deep venous system, accompanied by an inflammatory reaction of the adjacent perivascular tissues (notably, musculature), and mainly affects the lower extremities, but can compromise, although less frequently, the upper extremities. Its occurrence, especially in the hospital environment, is an important factor that can potentially increase the morbidity of the patients. DVT is also part of a more extensive syndrome—venous thromboembolism (VTE)—which is one of the main causes of intra-hospital death in the world today, killing more than others such as AIDS and cancer.